OP0251 Effects of 2 Years of Treatment with Romosozumab Followed by 1 Year of Denosumab or Placebo in Postmenopausal Women with Low Bone Mineral Density. (9th June 2015) - McClung, M.R.; Chines, A.; Brown, J.P.; Diez-Perez, A.; Resch, H.; Caminis, J.; Bolognese, M.A.; Goemaere, S.; Bone, H.G.; Zanchetta, J.R.; Maddox, J.; Rosen, O.; et al.
Abstract : Background: We previously reported that 1 year of treatment with the sclerostin antibody romosozumab (Romo) was associated with increased bone mineral density (BMD) and bone formation and with decreased bone resorption in postmenopausal women with low BMD. 1 Here, we report the results of 2 years of treatment with Romo, followed by 1 year of denosumab (DMAb) or placebo. Methods: This phase 2 study enrolled 419 postmenopausal women age 55 to 85 years with a lumbar spine, total hip, or femoral neck T-score ≤ –2.0 and ≥ –3.5. For the results described here, women received 1 of 5 regimens of Romo (70 mg QM, 140 mg QM, 210 mg QM, 140 mg Q3M, 210 mg Q3M; data for the 210 mg QM group are shown in the figure ) or placebo for 2 years. At the end of 2 years, eligible women entered a 1-year extension phase and were re-randomized 1:1 within their original treatment group to placebo or DMAb 60 mg Q6M. Only women who entered the extension were included in these analyses. Results: Romo led to rapid and marked increases in lumbar spine and total hip BMD during year 1 and continued increases through year 2. The largest gains were observed with Romo 210 mg QM, with BMD increases of 15.7% (lumbar spine) and 6.0% (total hip) (Figure ). Women receiving Romo 210 mg QM who transitioned to DMAb continued to accrue BMD at a rate similar to that in the second year of Romo; in those who transitioned to placebo, BMD returned toward pretreatment levels. Romo induced rapid stimulation of bone formation (P1NP) and decreased bone resorption (CTX). Increases in P1NP were transitory, returning toward baseline within 6 to 12 months and remaining below baseline through year 2. CTX remained below baseline through year 2. In women receiving Romo 210 mg QM who transitioned to DMAb, P1NP and CTX decreased; in those who transitioned to placebo, P1NP gradually returned to pretreatment levels, while CTX initially increased above baseline and gradually returned toward baseline. Adverse events were balanced between the placebo and Romo groups during the first 2 years of the study (with the exception of injection site reactions, most reported as mild) and in the placebo and DMAb groups during year 3. Conclusions: Romo led to rapid and marked increases in lumbar spine and total hip BMD over 2 years, which continued with DMAb and resolved after transition to placebo. These data suggest that the treatment effects observed with Romo are further augmented by follow-on treatments like DMAb. References: McClung MR, et al. N Engl J Med. 2014;370:412-420 Disclosure of Interest: M. McClung Grant/research support from: Amgen, Merck, Consultant for: Amgen, Lilly, Merck, A. Chines Shareholder of: Amgen, Employee of: Amgen, J. Brown Grant/research support from: Actavis, Amgen, Eli Lilly, Merck, Novartis, Consultant for: Amgen, Eli Lilly, Speakers bureau: Amgen, Eli Lilly, A. Diez-Perez Shareholder of: Active Life Scientific, Grant/research support from: Amgen, Consultant for: Amgen, Eli Lilly, Speakers bureau: Amgen, Eli Lilly, GSK, Novartis, ViiV, H. Resch: None declared, J. Caminis Shareholder of: UCB, Employee of: UCB, M. Bolognese Grant/research support from: Amgen, Regeneron, Eli Lilly, Speakers bureau: Amgen, S. Goemaere: None declared, H. Bone Grant/research support from: Amgen, Merck, Novartis, NPS, Consultant for: Amgen, Merck, Novartis, Tarsa, J. Zanchetta Grant/research support from: Amgen, MSD, Radius, Consultant for: Amgen, Eli Lilly, MSD, GSK, J. Maddox Shareholder of: Amgen, Employee of: Amgen, O. Rosen Shareholder of: Amgen, Employee of: Amgen, S. Bray Shareholder of: Amgen, Employee of: Amgen, A. Grauer Shareholder of: Amgen, Employee of: Amgen